2006
DOI: 10.1161/01.atv.0000200079.18690.60
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Carotid Plaque Area Test Is Superior to Other Noninvasive Atherosclerosis Studies for Reducing the Likelihood of Having Underlying Significant Coronary Artery Disease

Abstract: Objective-Coronary calcium score (CCS), carotid plaque area (CPA), intima-media thickness (IMT), and C-reactive protein (CRP) are independent predictors of cardiovascular prognosis. Although each test may enhance risk stratification, their comparative abilities to screen for underlying coronary stenoses in individual patients is less established. Methods and Results-Forty-two patients who had a 16-slice coronary computed tomography angiogram (CTA) performed were invited to have CPA, IMT, and CRP measured. CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 25 publications
2
64
0
4
Order By: Relevance
“…Several studies have provided evidence that carotid plaque predicts MI better than IMT. 14,31,35 It is also important to note, however, that many studies included plaque in the measurement of carotid IMT. [11][12][13][14]38 In some, the IMT measurement was dichotomized above and below a threshold level of IMT, which produced the effect of pooling subjects with plaques into the higher IMT level group because plaques tend to be more common in those with a thicker IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence that carotid plaque predicts MI better than IMT. 14,31,35 It is also important to note, however, that many studies included plaque in the measurement of carotid IMT. [11][12][13][14]38 In some, the IMT measurement was dichotomized above and below a threshold level of IMT, which produced the effect of pooling subjects with plaques into the higher IMT level group because plaques tend to be more common in those with a thicker IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that presence of carotid plaque was a more powerful predictor of cardiovascular events than intima-media thickness. [21][22][23][24] Carotid plaque score is useful as a means of semiquantitative analysis of degree of atherosclerosis. CPS is obtained by a wider range observation of the carotid arteries than intima-media thickness.…”
Section: Discussionmentioning
confidence: 99%
“…IMT primarily represents medial hypertrophy related to hypertension [24,25], and the association between IMT and CHD was weak in several studies [26,27]. CPA was claimed to be a better predictor of coronary atherosclerosis than other noninvasive methods [11,28]. CPA was also shown to be more sensitive than IMT for early detection of atherosclerosis [29].…”
Section: Discussionmentioning
confidence: 99%